2015
DOI: 10.1002/bio.3006
|View full text |Cite
|
Sign up to set email alerts
|

Luminescence study of Eu3+doped Li6Y(BO3)3 phosphor for solid‐state lighting

Abstract: In this study, Li6 Y1-x Eux (BO3 )3 phosphor was successfully synthesized using a modified solid-state diffusion method. The Eu(3+) ion concentration was varied at 0.05, 0.1, 0.2, 0.5 and 1 mol%. The phosphor was characterized for phase purity, morphology, luminescent properties and molecular transmission at room temperature. The XRD pattern suggests a result closely matching the standard JCPDS file (#80-0843). The emission and excitation spectra were followed to discover the luminescence traits. The excitatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(8 citation statements)
references
References 22 publications
0
8
0
Order By: Relevance
“…By monitoring at 612 nm attributed to 5 D 0 → 7 F 2 transitions of Eu 3+ ions, characteristic peaks from f–f transition of Eu 3+ and the O–Eu charge transfer band are observed in excitation spectra and it can be found that the intensity of the former transition is stronger than the later one, which makes Eu 3+ ‐doped precursor glass frit a potential luminescent material for solid‐state LED lighting . Beyond that, the excitation peaks located at 381 nm ( 7 F 0 → 5 L 7 ), 393 nm ( 7 F 0 → 5 L 6 ), and 465 nm ( 7 F 0 → 5 D 2 ) are greatly catered to the output wavelength of n‐UV or blue‐emitting LED chips and the emission peaks between 580 and 720 nm ( 5 D 0 → 7 F J , J = 0–4) indicate that it would be a good red‐emitting encapsulant for the PiG based WLEDs . Figure B shows the PL emission spectra with different Eu 3+ contents from 0.1 to 6 mol% excited at 393 nm.…”
Section: Resultsmentioning
confidence: 95%
“…By monitoring at 612 nm attributed to 5 D 0 → 7 F 2 transitions of Eu 3+ ions, characteristic peaks from f–f transition of Eu 3+ and the O–Eu charge transfer band are observed in excitation spectra and it can be found that the intensity of the former transition is stronger than the later one, which makes Eu 3+ ‐doped precursor glass frit a potential luminescent material for solid‐state LED lighting . Beyond that, the excitation peaks located at 381 nm ( 7 F 0 → 5 L 7 ), 393 nm ( 7 F 0 → 5 L 6 ), and 465 nm ( 7 F 0 → 5 D 2 ) are greatly catered to the output wavelength of n‐UV or blue‐emitting LED chips and the emission peaks between 580 and 720 nm ( 5 D 0 → 7 F J , J = 0–4) indicate that it would be a good red‐emitting encapsulant for the PiG based WLEDs . Figure B shows the PL emission spectra with different Eu 3+ contents from 0.1 to 6 mol% excited at 393 nm.…”
Section: Resultsmentioning
confidence: 95%
“…There are two strong emissions in the orange-red region coming from positions at 605 nm and 650 nm, corresponding to the 4 G5/2→ 6 H7/2 and 4 G5/2→ 6 H9/2 transitions of Sm 3+ , respectively [22]. Besides, there are two weak emissions centered at 566 nm and 714 nm, which can be assigned to the 4 G5/2→ 6 H5/2 and 4 G5/2→ 6 H11/2 transitions of Sm 3+ , respectively.…”
Section: Luminescent Propertiesmentioning
confidence: 99%
“…Among these narrow peaks the excitation peak at 395 nm is the most intense one which is attributed to 7 F 0 → 5 L 6 transition of Eu 3+ . Other peaks at 318, 363, 383, 418, and 466 nm were assigned to electronic transitions of 7 F 0 → 5 H 6 , 5 H 3 , 5 L 9 , 5 L 7 , and 5 D 3 respectively . This indicates that this particular phosphor can be successfully excited by 395 nm [near ultraviolet (UV)] as well as 466 nm [blue light emitting diodes (LEDs)].…”
Section: Resultsmentioning
confidence: 99%